Market bifurcations in board sports: How consumers shape markets through boundary work - Diaz Ruiz, Carlos; Makkar, Marian (Journal of business research, 2021)
The market-shaping literature recognizes that consumers are actors who can shape markets. However, research into the mechanisms of consumption-driven market-shaping is only emerging. This paper shows that one way in which consumers shape markets is through boundary work, as consumers make, break, and re-make the boundaries among multiple markets. Empirically, this paper investigates how user innovation practices catalyzed the formation of four boardsport markets: surfing, kitesurfing, windsurfing, and stand-up-paddling. The findings show that consumers shape markets in three steps: (1) generating local variations of consumption practices; (2) imposing order and coherence to intermediate frames; and (3) channeling creative consumption practices into market formation. This paper contributes to the market-shaping literature by conceptualizing how consumers splinter an existing singular market into new markets. We coin the term ‘market bifurcations’ to describe how a singular, seemingly cohesive consumer practice breaks down, splintering into several local variations, which can then catalyze the formation of new markets.